A modification of the CABARET scheme for numerical simulation of multicomponent gaseous flows in two-dimensional domains - Danilin, A.V.; Solovjev, A.V.; Zaitsev, A.M. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2015)
An explicit numerical algorithm for calculation of two-dimensional motion of multicomponent gas mixtures is proposed. A physical model as well as conservative and characteristic forms of governing equations are given. The discretization of the governing equations is made in accordance with the CABARET (Compact Accurately Boundary Adjusting-REsolution Technique) approach. The proposed algorithm is tested on problems of air shock waves passing through dense and dilute volume inhomogeneities with initial conditions adopted from numerical and experimental studies of other authors. A good agreement between the results of these studies and those obtained by the CABARET approach is shown.